2021
DOI: 10.1016/j.ijpam.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The risk of eating disorders among children and adolescents with attention deficit hyperactivity disorder

Abstract: Background and Objectives There are some studies on the association between attention deficit and hyperactivity disorder (ADHD) and the risk of eating disorders (ED). Only few have examined the risk of ED among children and adolescents with ADHD. Previous research which included subjects with ADHD with other comorbidities used inadequate controls and did not focus on the type of ADHD or the role of pharmacological treatment. Methods This matched cohort study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Similarly, a 2020 matched cohort screening study found the same three-fold increase—almost one third of children and adolescents with ADHD were at risk of ED, compared to 12% of healthy controls. Here, BMI was a statistically significant predictor of risk [ 247 ]. Impulsivity and inattention symptoms of childhood ADHD have been positively associated with the development of overeating and bulimic-type behaviours in adolescence [ 248 ].…”
Section: Personality Traits and Comorbid Mental Health Conditionsmentioning
confidence: 99%
“…Similarly, a 2020 matched cohort screening study found the same three-fold increase—almost one third of children and adolescents with ADHD were at risk of ED, compared to 12% of healthy controls. Here, BMI was a statistically significant predictor of risk [ 247 ]. Impulsivity and inattention symptoms of childhood ADHD have been positively associated with the development of overeating and bulimic-type behaviours in adolescence [ 248 ].…”
Section: Personality Traits and Comorbid Mental Health Conditionsmentioning
confidence: 99%
“…There have been few longitudinal studies to determine a causal relationship between EDs and obesity. Recently, a matched cohort study showed that children and adolescents with ADHD have a three-fold increased risk of ED compared to healthy controls (Jahrami et al, 2021).…”
mentioning
confidence: 99%